An epidemiologic analysis of diabetes in Colombia (2015)
The prevalence of diabetes has increased worldwide, leading to a massive social, economic, and health care burden. According to the International Diabetes Federation (IDF), 8.3% of the world's population experiences diabetes (382 million people); this figure is expected to rise to >592 million in <25 years, implying ≥175 million undiagnosed cases. Diabetes is most prevalent in the Western Pacific region with 138 million cases, followed by South East Asia with 72 million, Europe with 56 million, North America and the Caribbean with 37 million, the Middle East and Northern Africa with 35 million, South and Central America (SACA) with 24 million, and Africa with 20 million cases.